Seven Golden Steps for Performing Safe and Effective Percutaneous C-Arm-Guided Vertebral Intervention - Singh, Upinderjeet; Kumar, Nishith; Saifi, Alfa Shamim; Singh, Dharmendra Kumar (Indian Journal of Radiology and Imaging, 2024)
Percutaneous C-arm-guided diagnostic or therapeutic vertebral intervention has advantages of real-time monitoring of needle progression in vertebrae in craniocaudal or caudocranial angulation. To minimize the complications of nerve root or spinal cord damage, stepwise methodical intervention is pertinent. In this technical report, we demonstrate the seven golden steps for a safe and effective C-arm-guided vertebral intervention.
Keywords: vertebral intervention; C-arm fluoroscopy; vertebral augmentation